Degenerative Rotator Cuff Tears: Refining Surgical Indications Based on Natural History Data. Issue 5 (1st March 2019) - Keener, Jay D.; Patterson, Brendan M.; Orvets, Nathan; Chamberlain, Aaron M.
Abstract : Degenerative rotator cuff tears are the most common cause of shoulder pain and have a strong association with advanced aging. Considerable variation exists in surgeons' perceptions on the recommended treatment of patients with painful rotator cuff tears. Natural history studies have better outlined the risks of tear enlargement, progression of muscle degeneration, and decline in the function over time. This information combined with the known factors potentially influencing the rate of successful tendon healing such as age, tear size, and severity of muscle degenerative changes can be used to better refine appropriate surgical indications. Although conservative treatment can be successful in the management of many of these tears, risks to nonsurgical treatment also exist. The application of natural history data can stratify atraumatic degenerative tears according to the risk of nonsurgical treatment and better identify tears where early surgical intervention should be considered.